Developments in time-reversal of electromagnetic fields using the transmission-line modelling method - Scott, Ian (2010)
Inverse modelling methods are receiving significant interest, due to their simplicity and ease of use in the design of modern microwave components. This study investigates and further develops the technique of numerical time-reversal, in the context of automated component design, for modelling metal waveguide devices.